Pengaruh Promosi Kesehatan PHBS Melalui Video Animasi Terhadap Pencegahan Diare Pada Siswa SDN Wanajaya 04 Cibitung Kabupaten Bekasi Tahun 2021 - Ina Putri Parciti (2021)
RISKESDAS 2018 recorded that 12,806 West Java Province aged 5-14 years had diarrhea. Bekasi Regency 5,434 cases of diarrhea. There is a lack of knowledge of diarrhea and PHBS. The purpose of the study was to determine the effect of PHBS health promotion through animated videos on the prevention of diarrhea in increasing the knowledge of elementary school students. This type of quantitative research with pre-experimental method. The population of this research is the 5th and 6th grade students of SDN Wanajaya 04 Cibitung, Bekasi Regency. The research sample amounted to 165 respondents. Sampling technique with saturated sampling. Data analysis used the Wilcoxon Signed Ranks Test. The results of the study after health promotion through animated videos increased the average knowledge of students, diarrhea knowledge 4.45 to 4.70 and PHBS knowledge 8.19 to 9.39. Knowledge in both categories increased, diarrhea knowledge was 97.0% and PHBS knowledge was 88.5%. The p-value obtained is 0.000 <0.05. PHBS health promotion through animated video media on diarrhea prevention has a positive influence on students' knowledge. There is a significant increase in students' knowledge. It is expected that students can seek information on diarrhea and PHBS from various sources to prevent diarrhea properly.